Perspektif Kriminologi terhadap Kejahatan Seksual Anak dan Efektivitas Hukuman Kebiri Kimia - Musrinah Azzahra; Sofa Laela (LPPM Iblam School of Law, 2025)
Child sexual crimes are a serious issue that continues to rise in Indonesia, with perpetrators often coming from the victim's closest environment, such as teachers, neighbors, or even family members. This crime has severe consequences, including physical, psychological, and social impacts that hinder the victim's recovery and reintegration into society. To address this issue, the Indonesian government has implemented chemical castration as an additional punishment under Law No. 17 of 2016. However, the effectiveness of chemical castration remains debated, particularly regarding its long-term impact and ethical implications.This study employs a qualitative method with a normative legal approach, focusing on the analysis of regulations and legal interpretations in practice. Data were collected through a comprehensive literature review, including primary sources such as laws and court rulings, as well as secondary sources like academic journals and prior research. The findings indicate that child sexual crimes are influenced by psychological, social, and economic factors, requiring a multidisciplinary approach for prevention. While chemical castration may reduce recidivism by suppressing testosterone levels, its psychological impact on perpetrators and ethical concerns limit its effectiveness. Furthermore, alternative approaches such as psychological rehabilitation and cognitive behavioral therapy (CBT) have shown greater long-term success. Strengthening the legal system and enhancing public education on sexual violence prevention are crucial to reducing the prevalence of child sexual crimes.